Parametric analysis for interphase shear stress in MoS2/PET nanocomposite under thermo-mechanical loading - Rayka Vladova; Tatyana Petrova; Elisaveta Kirilova; Boyan Boyadjiev; Apostol Apostolov; Wilfried Becker; Alexsander Moravski (Acta Polytechnica CTU Proceedings)
In this study, a parametric analysis on the factors, that influence the value of theoretical interphase shear stress (ISS) in nanocomposite MoS2/PET, subjected to thermo-mechanical loading has been performed. The theoretical value of ISS is calculated based on obtained analytical solutions for the interfacial shear stress. The sensitivity of following parameters on the ISS in the considered nanostructure is investigated: the thicknesses of the nanocomposite layers, the length of the nanocomposite, the magnitude of the applied mechanical load, the applied temperature difference. It is found that the interface thickness does not affect the ISS value. The magnitude of the applied mechanical load has a strong influence on the magnitude of the ISS. The temperature difference (pure thermal loading) also affects the ISS value, but to a lesser extent. It should be noted, that in the case of combined loading (thermo-mechanical) the overall effect is additive. The thicknesses of MoS2 and PET mostly affect ISS, especially the substrate thickness. The obtained results are graphically illustrated and can be used for the fast prediction of ISS in micro scale in similar nanocomposite devices or parts thereof such as sensors, nano- and optical electronic devices, energy devices, etc.